Medication reconciliation as a strategy for preventing medication errors - Luana de Rezende Spalla; Selma Rodrigues de Castilho
ABSTRACT One of the current barriers proposed to avoid possible medication errors, and consequently harm to patients, is the medication reconciliation, a process in which drugs used by patients prior to hospitalization can be compared with those prescribed in the hospital. This study describes the results of a pharmacist based reconciliation conducted during six months in clinical units of a university hospital. Fourteen patients (23.33%) had some kind of problem related to medicine. The majority (80%) of medication errors were due to medication omission. Pharmaceutical interventions acceptance level was 90%. The results suggest that pharmacists based reconciliation can have a relevant role in preventing medication errors and adverse events. Moreover, the detailed interview, conducted by the pharmacist, is able to rescue important information regarding the use of drugs, allowing to avoid medications errors and patient injury.